Kontribusi faktor sosioekonomi pada kemiskinan di Pulau Jawa - Fadilla, Meita Indah; Hariyanti, Dini (Journal of Economics Research and Policy Studies, 2024)
Poverty is a social problem hindering a country's economic progress. This problem has spread widely and is increasingly complex throughout Indonesia, especially in Java Island, which has the fastest population growth and slow socio-economic development due to ongoing poverty. This research investigates the factors that influence poverty on Java Island in 2022. Using cross-section data from 119 districts/cities in Java Island and multiple linear regression analysis, this research measures poverty through the human development index, open unemployment rate, and minimum wage. The research results show that the open unemployment rate does not significantly affect poverty. In contrast, the human development index and regency/city minimum wages significantly negatively affect poverty. These findings suggest that improving human development in education, health, and decent living conditions is essential. In addition, the government needs to increase efforts in each region to tackle poverty effectively.